Diagnostic Criteria for Vestibular Migraine - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2013)
Investigators at the University of Pittsburgh, PA, review the latest clinical diagnostic criteria, pathophysiology, and treatment of vestibular migraine.